Hepatitis C virus infections among clients attending an HIV testing and counseling center in Dhaka, Bangladesh. Issue 2 (27th October 2017) - Rahman, Mustafizur; Hossain, Mohammad Enayet; Afrad, Mokibul Hassan; Hasan, Rashedul; Rahman, Mahfuza; Sarker, Md. Safiullah; Azim, Tasnim
Abstract : The prevalence of hepatitis C virus (HCV) and genotypes among 965 individuals attending an HIV testing and counseling unit in Dhaka Bangladesh during Jan‐Dec 2011 was determined. Anti‐HCV antibody was detected in 4.4% individuals; the highest rate 37.8% was in people who inject drugs (PWID) followed by that in the general population (1.3%) and less than 1% in other populations. HCV RNA was detected in 2.7%. The most common genotype was genotype 3 (88.5%) followed by genotype 1 (11.5%). A national wide surveillance for HCV infection reaching all key populations is required to assess the countywide burden and to develop appropriate treatment strategies.